Canned mussels packed in a blend of corn oil & coconut oil - Morada, Emma U.; Alabastro, Estrella F. (1983.)
The first phase was undertaken to determine the effect of smoking on the mussel meat prior to canning. A more acceptable product was obtained by smoking the mussel meat from one hour at 14°F prior to canning. The mean score overall acceptability of smoked mussel meat was 7.7 (between moderately and like very much), and 6;1 (like slightly) for unsmoked mussel meat. In the comparison of the experimental canned smoked mussels with a Spanish brand of canned mussels, sensory evaluation results showed that, in terms of flavor and texture, the former was significantly more preferred. In terms of color, it was the Spanish brand which was significantly more preferred than the other. Nevertheless, for overall acceptability, the experimental canned smoked mussels was significantly more preferred than the Spanish brand. The third phase, which was divided into two parts, was undertaken to determine: (a) the right blend of coconut oil with corn oil for a packing medium such that sensory characteristics are not significantly lowered; and (b) to determine the best processing time-temperature combination. Between the two oil combinations, 60-40% and 50-50% corn oil-coconut oil blend, the latter was found to have no significant difference from pure corn oil as packing medium in terms of flavor, odor, color of packing medium, and overall acceptability. From the study, it was also found that as the amount of coconut oil in the blend was increased, the absorption of oil by the smoked mussel meat also increased. Among the three time-temperature combinations employed fro the processing of smoked mussel meat in pure corn oil in 307x201.25 cans, i.e., 20 minutes at 250°F, 30 minutes at 240°F, 30 minutes at 250°F, 20 minutes at 250°F was determined to be the best, based on the F value of the process.
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Mussels